2014
DOI: 10.4172/1948-5948.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Combretum zeyheri and its S9 Metabolites against Escherichia coli, Bacillus subtilis and Candida albicans

Abstract: Citation: Masengu C, Zimba F, Mangoyi R, Mukanganyama S (2014) Inhibitory Activity of Combretum zeyheri and its S9 Metabolites against Escherichia coli, Bacillus subtilis and Candida albicans. AbstractMedicinal plants are therapeutic resources used by traditional population for health care, thus, it is important to evaluate the mechanism of action of herbal plants so as to validate their efficacy and avoid possible toxic effects. The water and methanol leaf extracts of Combretum zeyheri, medicinal plant from Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Candida albicans causes a number of non-life threatening conditions including vaginitis and oral thrush [ 3 ]. The fungi can also pass through the blood stream and may affect systemic organs including heart valves and this may be fatal especially in immunocompromised individuals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida albicans causes a number of non-life threatening conditions including vaginitis and oral thrush [ 3 ]. The fungi can also pass through the blood stream and may affect systemic organs including heart valves and this may be fatal especially in immunocompromised individuals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of mutant pathogenic strains that are resistant to current drugs, necessitates the need to find new, safe and effective drug compounds with minimum or acceptable side effects [ 4 ]. There are few effective antifungals available and most of them have unpleasant effects such as renal toxicity that occurs during the use of amphotericin B, and drug-drug interactions in the use of azoles [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combretum leprosum -derived triterpenes have been shown to have anti-inflammatory effects in mice [ 39 ]. Administration of Combretum zeyheri extracts to rats and subsequent isolation of metabolites, showed that the rat liver metabolites could inhibit the growth of microorganisms [ 40 ]. Using human recombinant hematopoietic prostaglandin D2 synthase (GST sigma), we have also shown that the Parinari curatellifolia leaf extract was the most potent plant extract (IC 50 = 3.8 μg/ml) to inhibit this enzyme in vitro [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Combretaceae family of plants has been widely used as traditional medicines [ 14 ]. Use of these plants to treat scorpion and snake bites, and mental problems and their use for the relief of sore throats and colds, fever, chest coughs associated with tuberculosis, pneumonia and venereal diseases like syphilis is common in most African communities [ 15 ]. Studies on the genus have shown presence of several phytochemical constituents including alkaloids, saponins, tannins and cardiac glycosides [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%